Proposal of a generic model to predict the time to reject low acid fruit pulps contaminated by Byssochlamys fulva - Paulo Ricardo Santos da Silva; Michele Bertoni Mann; Isabel Cristina Tessaro; Ligia Damasceno Ferreira Marczak (The Journal of Engineering and Exact Sciences)
A wide variety of microorganisms can contaminate food products. Due to low pH, fruits are mostly spoiled by fungi. The growth of fungi on fruits depends on the characteristics of the food and on environmental factors. In this context, the predictive microbiology is one option for studying and designing strategies to control microbial growth on foods. Thus, the aim of this work was to develop a model to predict the growth and the spoilage of low acid fruits contaminated by Byssochlamys fulva spores based on the storage temperature, pH and sugar content of the fruit. The growth behavior of this microorganism in modified potato-dextrose culture medium was studied as a function of temperature (20, 28, 36oC), pH (4, 5, 6) and sugar content (0, 5, 10, 15% m/v). A mathematical model was constructed to quantify the effect of these factors on the growth kinetics of this fungus and on the time to spoil the product, using linear model and Gibson-type model. The growth curves of B. fulva in pulps of mango, melon, papaya and tomato were obtained experimentally from which the time to spoil was determined and compared with the results predict by the mathematical model in the range of 20ºC to 36ºC. The developed model described satisfactorily the time to spoil, showing better results for melon pulp, for which the accuracy of the model was greater than 90%. The proposed model has a great potential to predict the shelf life of those foods contaminated by this fungus, mainly under lower storage temperature conditions.